Penerapan Metode Contextual Teaching Learning dalam Meningkatkan Keterampilan Berpikir Siswa pada Pembelajaran PAI - Anshori, Nanang; Subando, Joko (Lembaga Yasin AlSys, 2026)
The need to develop critical thinking skills in Islamic Religious Education (PAI) learning requires the application of approaches that can link religious content with everyday life contexts. This study aimed to analyze the implementation of the Contextual Teaching and Learning (CTL) method in improving students’ critical thinking skills in PAI learning. The research employed a qualitative approach with a literature study method through a review of books, scholarly articles, and relevant previous research. Data were analyzed using the Miles and Huberman model, which consists of data reduction, data display, and conclusion drawing. The findings showed that CTL plays a significant role in enhancing students’ critical thinking abilities. Before the application of CTL, PAI learning tended to be teacher-centered, so students were less able to analyze, evaluate, and relate religious concepts to everyday life contexts. After CTL was implemented, critical thinking indicators such as interpretation, analysis, evaluation, inference, problem solving, and argumentative communication improved. CTL components, including constructivism, inquiry, questioning, learning community, reflection, and authentic assessment, encouraged students to engage actively in learning and to build understanding in a contextual manner. This study concludes that CTL is an effective instructional approach for developing critical thinking skills in PAI learning. The implications of this study underscore the importance of consistent CTL implementation in PAI classrooms and the development of further contextual learning strategies that support the demands of 21st-century learning.